2021
DOI: 10.3390/plants10050877
|View full text |Cite
|
Sign up to set email alerts
|

Two Origins, Two Functions: The Discovery of Distinct Secretory Ducts Formed during the Primary and Secondary Growth in Kielmeyera

Abstract: Secretory ducts have been reported for more than 50 families of vascular plants among primary and secondary tissues. A priori, all ducts of a plant are of the same type, and only slight variations in the concentration of their compounds have been reported for few species. However, two types of secretion were observed in primary and secondary tissues of Kielmeyera appariciana, leading us to investigate the possible influence of duct origins on the structure and metabolism of this gland. Kielmeyera appariciana h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…2023 ). Internal mucilage is usually associated with water storage, protection from high irradiance, protection against herbivory (upon mechanical damage) and carbohydrate storage ( Fahn 1979 ; Gregory and Baas 1989 ; Costa et al . 2021 ; Fortuna-Perez et al .…”
Section: Discussionmentioning
confidence: 99%
“…2023 ). Internal mucilage is usually associated with water storage, protection from high irradiance, protection against herbivory (upon mechanical damage) and carbohydrate storage ( Fahn 1979 ; Gregory and Baas 1989 ; Costa et al . 2021 ; Fortuna-Perez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids produced by Protium species are considered responsible for deterrent actions against herbivores (Souza et al, 2016), and the phenolic compounds found in P. serratum have antioxidant activities (Tanamatayarat, 2016). The mucilage present in the secretions of species growing in dry environments, such as the Cerrado, also appear to aid in water retention (Silveira et al, 2020; Souza et al, 2020; Costa et al, 2021) and the proteolytic action of the proteins aids in controlling infections (Ramos et al, 2019). Plant secretions such as resins have important protective ecological roles.…”
Section: Discussionmentioning
confidence: 99%
“…11b). The cytoplasm of duct epithelial precursor cells is rich in organelles specialized in the synthesis of resin components, which gives those cells a dense and strongly stained appearance (Bhatt, 1987; Royo et al, 2015; Costa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the secretion of secretory ducts may be classified as resin, mucilage or gum [14,25] according to its composition. Mucilage ducts occur in Malvaceae [51] and Calophyllaceae [38]; resin ducts in Araceae [47], Clusiaceae [29] and Anacardiaceae [45]; and gum ducts in Calophyllaceae [38]. However, the complex composition of some resins, which confers white color to the exudate, has caused misinterpretation and has led some researchers to call it "latex", as in the case of Alismataceae ( [19,20], this study), Anacardiaceae [14,52,53] and Clusiaceae [14,44].…”
Section: Secretion Composition and Functionsmentioning
confidence: 99%
“…Laticifers and secretory ducts have been cited in at least 40 and 50 families, respectively, of vascular plants, including phylogenetically unrelated plants such as ferns, gymnosperms, and angiosperms, and they have emerged many times in the course of plant evolution [14,30,38]. Laticifers and secretory ducts have roles in herbivory reduction or resistance in plants.…”
Section: Introductionmentioning
confidence: 99%